Measuring Counterintuitiveness in Supernatural Agent Dream Imagery - Nordin, Andreas; Bjälkebring, Pär (Frontiers in Psychology, 2019)
The present article tests counterintuitiveness theory and methodology in relation to religious dream imagery using data on religious dream content. The endeavor adopts a “fractionated” or “piecemeal” approach where supernatural agent (SA) cognition is held to be a pivotal building block of purportedly religious dreaming. Such supernaturalistic conceptualizations manifests in a cognitive environment of dream simulation processes, threat detection and violation of basic conceptual categorization characterized by counterintuitiveness. By addressing SA cognitions as constituents of allegedly religious dream imagery, additional theorizing and supporting data is presented in a growing body of research in the Cognitive Science of Religion (e.g., Barrett, 2017; Barrett et al., 2009; Hornbeck and Barrett, 2013) and on religious dreaming (McNamara, 2016; McNamara and Bulkeley, 2015). The aim of the article is partly to map and align contemporary theorizing regarding counterintuitiveness and CI schemes with empirical qualification of the prosaic hypothesis about the predominance of supernaturalism in allegedly religious dreaming. This is done by (a) exploring the crucial topic of the pervasiveness of cognitive counterintuitiveness; (b) testing Barrett’s counterintuitiveness coding and quantifying scheme (CI scheme) for counterintuitiveness in the context of religious dreaming by assessing intercoder reliability; and (c) exploring the prevalence and base rate frequency of counterintuitiveness in dream reports. This undertaking aims to contribute to the methodology and understanding of religious dream cognition, as well as to establish the cross-cultural base rates of counterintuitiveness in dreams for future research.